2017
DOI: 10.1021/acs.nanolett.7b02434
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Distribution of Electrons Emitted from Resonantly Excited Individual Gold Nanorods

Abstract: Electron emission by femtosecond laser pulses from individual Au nanorods is studied with a time-of-flight momentum resolving photoemission electron microscope (ToF k-PEEM). The Au nanorods adhere to a transparent indium-tin oxide substrate, allowing for illumination from the rear side at normal incidence. Localized plasmon polaritons are resonantly excited at 800 nm with 100 fs long pulses. The momentum distribution of emitted electrons reveals two distinct emission mechanisms: a coherent multiphoton photoemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 60 publications
2
34
0
1
Order By: Relevance
“…Metal nanostructures, such as nanotips, nanowires, nanospheres, nanorods, nanotriangles, nanostars, and composite bow‐tie and nanorod antennae,[36,45b,53,62] are of particular interest for OFE experiments due to their relatively simple electronic structures and strong plasmonic near‐field enhancement. Many novel electron dynamics phenomena have been discovered during the investigation of OFE from metallic tips in this way.…”
Section: State‐of‐the‐art Ultrafast Field‐emission Sourcesmentioning
confidence: 99%
“…Metal nanostructures, such as nanotips, nanowires, nanospheres, nanorods, nanotriangles, nanostars, and composite bow‐tie and nanorod antennae,[36,45b,53,62] are of particular interest for OFE experiments due to their relatively simple electronic structures and strong plasmonic near‐field enhancement. Many novel electron dynamics phenomena have been discovered during the investigation of OFE from metallic tips in this way.…”
Section: State‐of‐the‐art Ultrafast Field‐emission Sourcesmentioning
confidence: 99%
“…In this regard, Zijlstra and co-workers have explored the optical properties of gold nanorods and exploited their potentials for single-molecule sensing. [11,12,26,31,32] In the same fashion, Sönnichsen et al have explored the fundamental plasmonics of gold and silver nanorods [33][34][35][36] with the ultimate goal of developing label-free plasmonic biosensors [37][38][39][40] for various purposes including rapid detection of analytes [41] and monitoring the intrinsic dynamics as well as spatial patterns of biomolecules. [42][43][44] Specifically, Amet et al demonstrated using Au nanoparticles for label-free detection of single molecules with very high temporal resolution.…”
Section: Plasmonic Nanoparticles For Single-molecule Detectionmentioning
confidence: 99%
“…Une première approche de ce type, conduite sur un film Au monocristallin, est rapportée figure 3 Une première illustration de ces tendances est rapportée figure 4.1. L' étude en question porte sur le suivi, dans l' espace réciproque, de la distribution en moments et en énergie des électrons émis par un unique bâtonnet d'or à la résonance plasmon [6]. Elle est conduite sur un instrument à détection d' électrons par temps de vol.…”
Section: Coupler Les Photons Aux éLectrons Dossierunclassified